Label-free metabolic imaging of Pseudomonas aeruginosa infection using two-photon fluorescence lifetime imaging microscopy - Snyder, Greg A.; Bergamin de Castro, Tialfi; Scott, Alison J.; Ray, Krishanu (Frontiers in Cellular and Infection Microbiology, 2025)
In this study we have applied high-spatial and temporal label-free imaging of individual live multidrug-resistant bacteria and bacteria-infected cells and animal tissue using two-photon fluorescence lifetime imaging microscopy (2p-FLIM). 2p-FLIM can identify and quantify fluorescence intensity and lifetimes among bacteria, infected cells, and tissues. We have implemented 2p-FLIM in combination with phasor plot analysis for quantifying molecular differences of NAD(P)H intensities and lifetimes for fast, sensitive, high-resolution, non-destructive imaging of live bacteria and bacteria-infected cells and tissues. We have further developed a coordinated workflow using 2p-FLIM for high-resolution temporal-spatial mapping of bacteria infected cells and tissues that can be performed for near real-time quantitation of NAD(P)H intensities and lifetimes for identifying changes in metabolism. 2p-FLIM may have broad applicability for characterizing microbial infection at the molecular, subcellular, cellular and tissue levels. The ability to quantitate and directly monitor changes in NAD(P)H metabolism in near real-time in bacteria cells and tissues during an infection, offers a potential mechanism for understanding microbial pathogenesis and evaluating therapeutic treatments that can be applied to multiple model systems. Overall, the application of this label-free imaging approach has the potential to address biomedical research needs and technical problems that occur broadly across multiple biological systems and diseases.